Allocation of the “Already” Limited Medical Resources Amid the COVID-19 Pandemic, an Iterative Ethical Encounter Including Suggested Solutions From a Real Life Encounter - Alhalaseh, Yazan Nedal; Elshabrawy, Hatem A.; Erashdi, Madiha; Shahait, Mohammed; Abu-Humdan, Abdulrahman Mohammad; Al-Hussaini, Maysa (Frontiers in Medicine, 2021)
The shortage of healthcare providers is well documented in low-income countries (LIC) prior to COVID-19, due to various causes including the migration to developed countries, scarcity of supplies, poor healthcare infrastructure, limited ICU facilities, and lack of access to guidelines and protocols. One of the important hitches in LIC is the insufficient testing capacity that precluded accurate assessment of disease burden and subsequently resource allocations. Trying to adhere to the principles of bioethics including respect to others, beneficence, and justice should be applied on the ground in the particular setting of the LIC. Solutions should be tailored to the tangible needs and possibility of implementation in real life in the face of the “already” limited resources by making use of simple, yet plausible, measures. Implementing guidelines and frameworks that were set to work in the better-resourced nations is a call for futility. The adoption of novel solutions to overcome the unique challenges in the LIC is exigent. These include the use of automated screening algorithms and virtual video clinics. Moreover, integrating electronic intensive care unit (e-ICU) software may allow for remote monitoring of multiple patients simultaneously. Telemedicine could help in getting consultations worldwide. It can also enhance healthcare workers’ knowledge and introduce new skills through teleconferences, e-workshops, and free webinars. Healthcare workers can be remotely trained to enhance their skills. Agencies, such as the WHO, should develop comprehensive programs to tackle different health issues in LIC in collaboration with major institutions and experts around the world.